Aeroelastic simulation of rotorcraft propulsion systems - Castillo Pardo, Alejandro (Cranfield University, 2017)
A close relationship between the aerospace technology level and the capability to model and simulate the physics involved during the flight has been identified throughout the aviation history. The continuous improvement in physical and mathematical models has provided a further understanding of the behaviour of the different components along with the complete vehicle. As a result, the performance modelling has experienced a large improvement. The aviation industry, which is characterised by the use of cutting edge technology, requires large investments when new concepts are introduced. The application of high fi delity simulation tools reduces considerably the investment carried out prototyping and testing. This fact is also applicable to the rotorcraft industry, where a continuous increase in the employment of helicopters has been observed throughout the last decades, expecting a sharp growth within the next 20 years. The forecasted growth in the number of helicopter operations along with the increasing concern about the environmental impact of aviation, lead the governmental bodies to set up a number of goals to reduce the carbon dioxide, nitrogen oxides, and noise emissions. Three paths were identified to reduce the environmental impact and meet the proposed goals. The fi rst one is the reduction in the number of operations. However, a sharp growth in the number of helicopter operations is expected. The second one is the optimisation of the flight procedures. Nevertheless, the potential improvement is limited. The third one is the introduction of a quieter and more,efficient type of rotorcraft. There exist two new rotorcraft con figurations which show enough potential to be studied. These are the tilt-rotor and compound helicopter. Both designs improve the cruise performance using auxiliary lift and propulsive systems, while they still exploit the vertical flight capability of helicopters. Nevertheless, the lack of reliable high fi delity models has made their development long and highly expensive. Within this context, the necessity of a simulation framework able to simulate and predict the detailed performance of novel rotorcraft con figurations is highlighted. The present work aims to lay the foundations of this comprehensive rotorcraft code by developing a computational framework for the aeroelastic simulation of propulsion systems. The tool is characterised by a high fi delity level able to predict the highly unsteady loads at a low computational cost. The fi rst characteristic makes this tool suitable for the design stage and noise calculations; whilst the second one enables its integration into multidisciplinary optimisation procedures. The development of this framework has required a considerable contribution to the knowledge in different areas of study, these included: structural dynamics, in flow aerodynamics, blade aerodynamics, aeroelasticity, and computational acceleration techniques. The individual models have been integrated into a cost efficient aeroelastic simulation framework, which has been extensively validated with experimental data. Very good and in some cases excellent correlation with the experimental measurements has been observed. The main contribution of this work has been the successful development of a computational framework for the aeroelastic simulation of rotorcraft propulsion systems. It accurately simulates and predicts the aerodynamic flow field and the unsteady loads generated by the rotor and transferred to the fuselage. It is easily expandable to account for interactions with other rotors, auxiliary lift surfaces, and fuselage bodies. The simulation tool estimates high fidelity low and high frequency aerodynamic loading, which enables the calculation of impulsive noise emissions. The framework computes accurate predictions of rotor power required, which enables its use as a validation tool for lower order models. The developed framework approximates the third level of Padfi eld's hierarchical paradigm, providing detailed aeroelastic information necessary for design purposes. The additions of parallel computing and an acceleration scheme results in a highly computationally effcient tool suitable for optimisation methodologies. Moreover, a considerable contribution has been made in terms of modelling of: coupled modal characteristics, aeroelastic simulation; computational enhancements of in flow models and investigation of the effect of the fuselage aerodynamic interference and coupled flexible blade modelling.